2017
DOI: 10.5539/jas.v9n4p1
|View full text |Cite
|
Sign up to set email alerts
|

Echinacea purpurea Extract Affects the Immune System, Global Metabolome, and Gut Microbiome in Wistar Rats

Abstract: Echinacea purpurea extract, a traditional herbal food additive with dual-purpose of medicine and edible material, has been widely used for the treatment and prevention of various infectious diseases, especially for children, old aged and immunocompromised patients. Although there were numerous reports suggested E. purpurea possessed immunostimulatory and antibacterial effects in vitro, the mechanisms underlying remained to be elucidated. This study employed immunologic factors analysis, GC-TOFMS based metabolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Administration of E.P. decreases IL-6 and TNF-α result go in hand with results obtained by Wang et al [24] that confirmed the positive impact of E. P. on the immune system. Similarly, CeONPs treatment lowered levels of pro-inflammatory cytokines, IL-6 and TNF-α which in agreement with [12] .…”
Section: Discussionsupporting
confidence: 81%
“…Administration of E.P. decreases IL-6 and TNF-α result go in hand with results obtained by Wang et al [24] that confirmed the positive impact of E. P. on the immune system. Similarly, CeONPs treatment lowered levels of pro-inflammatory cytokines, IL-6 and TNF-α which in agreement with [12] .…”
Section: Discussionsupporting
confidence: 81%
“…Also, preparations obtained from Echinacea purpurea (E. purpurea) leaves showed antibacterial, antifungal, antiviral, antiparasitic, immunomodulatory, anti-inflammatory and antioxidant effects, explaining its popular use against many infectious diseases for hundreds of years [24][25][26][27] . Echinacea was also used as a food supplementary, helping in treatment and prevention of many infections, especially in children, old aged and immunocompromised patients [28,29] . Extracts from Echinacea leaves decrease Cox-2 in a concentration dependent manner and interfere with IL-17 production [30,31] .…”
Section: Effects Of Echinacea Purpurea In Murine Cryptosporidiosismentioning
confidence: 99%
“…As major immunomodulatory mechanisms, they act especially as boosters of immune system, through the stimulation of both innate and adaptive humoral and cellular immunity ( Table 1 ). However, further mechanisms, such as an interference with proinflammatory pathways and a modulation of the gut microbiome, have been reported [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…and E. angustifolia DC), characterized by immunostimulant properties on both innate and adaptive response, associated with antiviral, antinflammatory and antimicrobial effects [ 42 ]. More recently, its ability to indirectly boost the immune system, through the modulation of gut microbiome, has been highlighted [ 18 ]. All the phytocomplex seems to be involved in these properties, however, alkylamides and purified polysaccharides have been found to induce immunomodulatory effects [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%